The Genesis of Technoscientific Revolutions Rethinking the Nature and Nurture of Research - Narayanamurti, Venkatesh (Harvard University Press, 2021)
Research powers innovation and technoscientific advance, but it is due for a rethink, one consistent with its deeply holistic nature, requiring deeply human nurturing. Research is a deeply human endeavor that must be nurtured to achieve its full potential. As with tending a garden, care must be taken to organize, plant, feed, and weed-and the manner in which this nurturing is done must be consistent with the nature of what is being nurtured. In The Genesis of Technoscientific Revolutions, Venkatesh Narayanamurti and Jeffrey Tsao propose a new and holistic system, a rethinking of the nature and nurturing of research. They share lessons from their vast research experience in the physical sciences and engineering, as well as from perspectives drawn from the history and philosophy of science and technology, research policy and management, and the evolutionary biological, complexity, physical, and economic sciences. Narayanamurti and Tsao argue that research is a recursive, reciprocal process at many levels: between science and technology; between questions and answer finding; and between the consolidation and challenging of conventional wisdom. These fundamental aspects of the nature of research should be reflected in how it is nurtured. To that end, Narayanamurti and Tsao propose aligning organization, funding, and governance with research; embracing a culture of holistic technoscientific exploration; and instructing people with care and accountability